Evaluation of procedural pain for neonates in a neonatal intensive care unit: a single-centre study - Yun Pan; Lingli Mei; Shuohui Chen; Xiaofei Chen; Feixiang Luo; Huaiyu Zhu; Qi Shu; Xiaoying Cheng; Yisheng Zhao (BMJ Publishing Group, 2023)
Background To evaluate the procedural pain experienced by neonates in a neonatal intensive care unit (NICU) setting and determine the corresponding pain grades.Methods Two experienced nurses independently used the Neonatal Infant Pain Scale (NIPS) to evaluate the neonatal pain during procedures taking place in the tertiary NICU and two level-two neonatal care units in the Children's Hospital of Zhejiang University School of Medicine. The mean and distribution of NIPS pain scores and the corresponding pain grades of participants when experiencing clinical painful procedures were analysed.Results A total of 957 neonates exposed to 15 common clinical painful procedures were included in the study. The clinical painful procedures experienced by 957 participants could be divided into three groups: severe pain (NIPS score 5-7: peripheral intravenous cannulation, arterial catheterisation, arterial blood sampling, peripherally inserted central catheter placement and nasopharyngeal suctioning), mild to moderate pain (NIPS score 3-4: finger prick, intramuscular injection, adhesive removal, endotracheal intubation suctioning, heel prick, lumbar puncture and subcutaneous injection) and no pain to mild pain (NIPS score 0-2: gastric tube insertion, enema and intravenous injection).Conclusions The neonatal pain response to clinical procedures in NICU had certain pattern and preintervention drug analgesia could be taken for painful procedures with clustered high NIPS pain scores. Meanwhile, full coverage non-drug pain relief measures could be taken for procedures that are with scattered pain scores, and real-time pain evaluation should be provided to determine whether further drug analgesia is required.